2006
DOI: 10.1111/j.1469-0691.2006.01445.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk-factors among patients with Crimean-Congo haemorrhagic fever virus infection: severity criteria revisited

Abstract: The aim of this study was to determine the predictors of mortality among patients infected with Crimean-Congo haemorrhagic fever (CCHF) virus. Among patients with acute febrile syndrome, characterised by malaise, bleeding, leukopenia and thrombocytopenia, who were admitted to hospital during the spring and summer of 2002-2004, 54 had positive IgM and/or PCR results for CCHF virus in blood or tissue. The overall case fatality rate was 7.4%. Among the fatalities, haematemesis (p 0.009), melaena (p 0.001) and som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
182
3
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(208 citation statements)
references
References 12 publications
15
182
3
8
Order By: Relevance
“…Early studies in South Africa found that most patients who went onto survive the disease had detectable anti-CCHFV IgM by day 7 and IgG by day 7-9 of illness, while no response was detected in fatally infected individuals (Burt et al, 1994;Shepherd et al, 1989c;van Eeden et al, 1985b). The correlation of antibody responses with survival has been demonstrated more recently in patients in Turkey and Kosovo (Ergonul et al, 2006a;Saksida et al, 2010).…”
Section: Predictors Of Survival or Deathmentioning
confidence: 93%
See 1 more Smart Citation
“…Early studies in South Africa found that most patients who went onto survive the disease had detectable anti-CCHFV IgM by day 7 and IgG by day 7-9 of illness, while no response was detected in fatally infected individuals (Burt et al, 1994;Shepherd et al, 1989c;van Eeden et al, 1985b). The correlation of antibody responses with survival has been demonstrated more recently in patients in Turkey and Kosovo (Ergonul et al, 2006a;Saksida et al, 2010).…”
Section: Predictors Of Survival or Deathmentioning
confidence: 93%
“…Experience over the past decade in Turkey has shown that gingival bleeding, ecchymoses, hematemesis, diarrhea, melena, confusion and somnolence are significantly more common in fatal cases (Ergonul et al, 2006a;Cevik et al, 2008;Hatipoglu et al, 2010). Lethal illness was associated with more severe thrombocytopenia, more prolonged PT and aPTT, lower fibrinogen levels and increased serum AST and ALT (Ergonul et al, 2006a;Ozkurt et al, 2006;Onguru et al, 2010).…”
Section: Predictors Of Survival or Deathmentioning
confidence: 99%
“…Serum ChT could be a prognostic marker in patients with CCHF. Different predictors of fatality were reported as risk factors for CCHF (27,(29)(30)(31)(32), and those previously defined severity criteria were not always consistent. These criteria include decreased platelet counts, prolonged aPTT, increased AST, ALT and LDH activities in a univariate analysis from five different studies.…”
Section: Discussionmentioning
confidence: 83%
“…Daha önceki yayınlarda, bildirilen taşikardi, nabızda düzensizlikler, ağız kuruluğu, saç dökülmesi, polinörit görme bozukluğu gibi bulguların hiçbirisi son yayınlarda belirtilmemiştir (2,5,13,(29)(30)(31) .…”
Section: Klinik Bulgularunclassified